Digital alkali resist prints on polyester. (5th September 2017) - Lewis, David M.; Broadbent, Peter J.
Abstract : In earlier papers we have described sulphite‐based and secondary amine‐based resist printing of cotton using ink‐jet procedures. This paper describes the chemical resist printing of polyester fabrics padded with disperse dyes to create a white image on a coloured background. Polyester grounds have been prepared by the pad‐dry 'dyeing' of polyester fabrics with alkali‐clearable disperse dyes, such as a Dianix PC (DyStar) or a Dianix SF (DyStar) dye, and subsequently ink‐jet printed with sodium carbonate based ink formulations to yield a white image on a solid ground following high temperature steaming and appropriate wash‐off procedures. Coloured images have been achieved by a two‐step process whereby the coloured ground fabric was initially printed with an alkali‐based ink and then overprinted in a second step with an illuminating ink formulation containing an alkali stable disperse dye, such as a Dianix AD (DyStar) or Serilene ADS (Yorkshire Chemicals).